2011
DOI: 10.1148/radiol.10100328
|View full text |Cite
|
Sign up to set email alerts
|

The Mammographic Density of a Mass Is a Significant Predictor of Breast Cancer

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.10100328/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 22 publications
(24 reference statements)
7
30
0
Order By: Relevance
“…67.4% of the subjects of our study had highdensity and it was comparable with a study done in USA in which 70.2% had highdensity masses 23 . The UK study however did not favour this finding, as they could not find a difference of density between invasive lobular carcinoma (ILC) and IDC subjects 14 .…”
Section: Resultssupporting
confidence: 90%
“…67.4% of the subjects of our study had highdensity and it was comparable with a study done in USA in which 70.2% had highdensity masses 23 . The UK study however did not favour this finding, as they could not find a difference of density between invasive lobular carcinoma (ILC) and IDC subjects 14 .…”
Section: Resultssupporting
confidence: 90%
“…We also found that a high mammographic density was correlated with malignancy ( Fig. 2), in agreement with a study by Woods et al (2011). Some investigators (Egan 1988;Homer 1997;Kopans 2007) proposed that high-density lesions were more likely to be malignant because of dense cellular components and reactive fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…15,16 A recent report suggests that, in addition to irregular mass shape, speculated mass margin, and patient age, an increase in mammographic attenuation of a mass also increases its likelihood of malignancy. 17 However, high mass density by itself is not sufficiently accurate to avert the need for a biopsy. If lesions could be characterized quantitatively according to their chemical compositions, predictive capability might be improved.…”
Section: Introductionmentioning
confidence: 99%